Stabilitas Fisik dan Efektivitas Sediaan Tabir Surya Kombinasi Oksibenson dan Oktil Metoksisinamat dalam Basis Gel Carbomer 940 dengan Penambahan Asam Glikolat - Rosita, Noorma; Purwanti, Tutiek; Agustin, Agustin (UI Scholars Hub, 2010)
To fulfill the consumer expectation, cosmetic industries mostly add glycolic acid as whitening agent to the sunscreen preparation. The aim of this research was to know the effect of glycolic acid addition with the concentration of 8, 10, and 12% w/w on physical stability and effectiveness of sunscreen product containing oxybenzone and octyl methoxycinnamate (2: 7% w/w) in carbomer 940 gel. The physical stability test was done by observing physical appearance, pH, and spreading ability during 60 day storages on zone IV condition (temperature 30±0.5° and RH 70±2%). The efficacy was determinated base on SPF (Sun Protection Factor) value by spectrophotometer. The result of the physical stability test showed that glycolic acid addition affects the physical appearance (consistency) of sunscreen product, but pH and spreading ability are relatively stable. The efficacy test result showed that the addition of glycolic acid has an effect on SPF value of sunscreen product. Product which combined with glycolic acid showed a significant increase of SPF value, compared to control formula. The addition of glycolic acid increased SPF value and alter the effectiveness category from extra protection to maximal protection.